2018
DOI: 10.1186/s13063-018-2905-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of sucrose gel and metronidazole gel in treatment of clinical symptoms of bacterial vaginosis: a randomized controlled trial

Abstract: BackgroundLactobacilli, as normal vaginal flora, have a central role in controlling body environment and preventing the growth of pathogens. Sucrose, by promoting the growth of Lactobacilli, accelerates the suppression of pathogenic bacteria. The aim of this research was to compare the effects of sucrose gel with those of metronidazole gel in treating women with bacterial vaginosis (BV).MethodsThis triple-blind clinical trial (IRCT2016112631105N1) was conducted with 70 sexually active, premenopausal women diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
9
2
Order By: Relevance
“…Despite previously reported positive results for this intervention(22,23), we found no clinical or microbial indications of improvement. In our hands, intravaginal sucrose gel did not lower vaginal pH, Nugent scores, or Amsel criteria positivity.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Despite previously reported positive results for this intervention(22,23), we found no clinical or microbial indications of improvement. In our hands, intravaginal sucrose gel did not lower vaginal pH, Nugent scores, or Amsel criteria positivity.…”
contrasting
confidence: 99%
“…Clinical trials are currently underway to test the use of intravaginal Lactose (NTC03878511), Glucose (NCT03357666), and Glycogen (NCT02042287) to treat BV symptoms. Sucrose in particular has shown potential for improving clinical markers of BV in humans (22) and shifting the VM of rhesus macaques (23). However, the clinical study only examined changes in clinical symptoms and Amsel criteria at one-time point after 14 days of treatment and did not interrogate changes in microbial communities (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated no significance difference in the effectiveness of both the gels. This trial opens the new possibility of BV treatment compared to conventional treatment [169]. Similarly, the safety and efficacy of boric acid-based vaginal gel (TOL-463) was investigated for the treatment of BV with enhanced antibiofilm activity.…”
Section: Progresses Of Advanced Drug Delivery In Clinical Researchmentioning
confidence: 99%
“…A triple-blind trial on sucrose vaginal gel compared with metronidazole gel found no difference in the reduction of clinical complaints or elimination of Amsel criteria. 101 A study of 189 women with BV evaluating a higher dose metronidazole gel (1.3%) for 1, 3, and 4 days compared with standard 5-day treatment with metronidazole gel (0.75%) found that treatment with 1.3% gel demonstrated similar efficacy, safety and tolerability compared with treatment with 0.75% gel. 102 …”
Section: Treatmentmentioning
confidence: 99%